Tumor Microenvironment Status Predicts the Efficacy of Postoperative Chemotherapy or Radiochemotherapy in Resected Gastric Cancer - Duan, Ran (Front Immunol, 2021)
PURPOSE: Chemotherapy (CT) and radiochemotherapy (RCT) are currently the standard postoperative treatments for resected gastric cancer (GC). However, owing to a lack of predictive biomarkers, their efficacy is currently suboptimal. As tumor microenvironment (TME) has the potential to determine treatment response, we investigated the association of TME status with the efficacy of fluoropyrimidine (FU)-based postoperative CT/RCT in resected GC. METHODS: Patients with transcriptome data were screened and selected in three independent cohorts. Favorable (fTME) and poor TME (pTME) were defined by a transcriptome-based TME qualification method. Immune infiltration and hypoxia were assessed. RESULTS: A total of 535 patients were eligible. fTME, indicating the presence of immune activation, was characterized by NK cell rather than CD8+ T cell infiltration. However, postoperative CT/RCT improved overall survival and disease-free survival time more evidently in patients with pTME GC than those with fTME GC. Stratified by stage in fTME GC, stage III patients benefited from postoperative CT/RCT while stage Ib/II patients did not. In comparison, patients with pTME GC benefited from postoperative CT/RCT, regardless of stage. Furthermore, fTME was more hypoxic than pTME, accompanied by a stronger expression of thymidylate synthase (TS)—the target of FU. Stage Ib/II fTME GC was the most hypoxic and had the strongest TS expression across all the subgroups stratified by TME status and stage. CONCLUSIONS: We found that fTME, with the enrichment of NK cells, may predict the lack of postoperative CT/RCT efficacy in stage Ib/II GC, which may be associated with hypoxia and TS expression. Further validations and mechanism researches are needed.